PERLINDUNGAN HUKUM BAGI KREDITUR ATAS PEMBEBANAN HAK TANGGUNGAN AKIBAT PEMBATALAN SERTIPIKAT - Christian Alexander P Siregar; Wira Franciska; Iran Sahril (Journal of Innovation Research and Knowledge, 2025)
In everyday life, problems often occur related to the existence of objects of ownership of rights obtained unlawfully whose guarantees often become problems regarding the truth of the objects of guarantee as regulated in Law of the Republic of Indonesia Number 4 of 1996 concerning Mortgage Rights over land and the land in question. often becomes the object of bank guarantees which will be burdened with Mortgage Rights. Problem Formulation What are the legal consequences for creditors of the cancellation of property rights certificates that are encumbered with Mortgage Rights and how to provide legal protection to creditors for cancellation of property rights certificates that are the object of Mortgage Security. Theory of legal protection According to Satijipto Raharjo, theory of legal consequences according to Soeroso.R The method used in this study is a type of normative juridical research, namely literature law research or secondary data with primary, secondary and tertiary legal sources. The research approach used is a legislative, analytical, conceptual and case approach. The technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, literature, books, journals and other sources of legal materials. For legal material analysis techniques, it is carried out by grammatical and systematic legal interpretation as well as legal construction methods, analogies, and legal refinement. Research results: Protection for creditors against cancellation of mortgage certificates that have been encumbered with mortgage rights in the form of preventive and repressive protection. Preventive protection in the Mortgage Rights Law does not yet accommodate the regulation that canceling a certificate based on a Court Decision does not result in the cancellation of the Mortgage Rights that burden it, so that the bank as the creditor is not harmed. Repressive legal protection if the debtor defaults or defaults on the promise of his debts and receivables, the bank can also file a civil lawsuit against the debtor's debt to the creditor or take the path of peace through non-litigation. The legal consequence for creditors is that the removal of the title certificate which is the object of collateral for mortgage rights also removes the right of precedence in payment of the debtor's debt in the event of default.